1998
DOI: 10.1073/pnas.95.6.2967
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and cytoplasmic free calcium level changes induced by elastin peptides in human endothelial cells

Abstract: The extracellular matrix protein ''elastin'' is the major component of elastic fibers present in the arterial wall. Physiological degradation of elastic fibers, enhanced in vascular pathologies, leads to the presence of circulating elastin peptides (EP). EP have been demonstrated to inf luence cell migration and proliferation. EP also induce, at circulating pathophysiological concentrations (and not below), an endothelium-and NO-dependent vasorelaxation mediated by the 67-kDa subunit of the elastin-laminin rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Cell responses to EDPs were often attributed to the binding of a VGVAPG hexapeptide sequence, repeated several times in tropoelastin, the soluble precursor form of elastin, to a unique sequence of S-Gal, encoded by the frame shifted exon 5 of β-galactosidase. Previous investigations indicated that the VGV tripeptide could represent the core sequence in EDPs, mediating their potent influence on vascular tone through increased intracellular calcium in endothelial cells (Faury et al, 1995;Faury et al, 1998a;Faury et al, 1998b). Conversely, a type VIII β-turn conformation adopted by elastin peptides with the GXXPG sequence was mainly involved in directing matrix metalloproteinase expression in fibroblasts and fibrosarcoma cells in culture Huet et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell responses to EDPs were often attributed to the binding of a VGVAPG hexapeptide sequence, repeated several times in tropoelastin, the soluble precursor form of elastin, to a unique sequence of S-Gal, encoded by the frame shifted exon 5 of β-galactosidase. Previous investigations indicated that the VGV tripeptide could represent the core sequence in EDPs, mediating their potent influence on vascular tone through increased intracellular calcium in endothelial cells (Faury et al, 1995;Faury et al, 1998a;Faury et al, 1998b). Conversely, a type VIII β-turn conformation adopted by elastin peptides with the GXXPG sequence was mainly involved in directing matrix metalloproteinase expression in fibroblasts and fibrosarcoma cells in culture Huet et al, 2002).…”
mentioning
confidence: 99%
“…In addition, EDPs, at a concentration averaging that present in the circulation (Kucich et al, 1983;Fülöp et al, 1990), activate low specificity calcium channels in human umbilical venous endothelial cells (HUVECs), leading to an enhancement of cytoplasmic and nuclear-free calcium concentration (Faury et al, 1998a). Such modifications in calcium flux induce an endotheliumdependent vasodilatation that can be suppressed by an inhibitor of nitric oxide production (Faury et al, 1995;Faury et al, 1998a;Faury et al, 1998b).…”
mentioning
confidence: 99%
“…Human umbilical venous endothelial cells (HUVEC) were isolated using a technique adapted from Jaffe et al (19,29). Cells were harvested from the umbilical vein by a 10-min incubation at 37°C with collagenase 1A and cultured in 0.25 mg/ml human fibronectincoated dishes in medium 199 containing 22% human serum, streptomycin (0.1 mg/ml), penicillin (100 UI/m), and L-glutamine (2 mmol/ l).…”
Section: Cell Culturementioning
confidence: 99%
“…Then, NO production induces a short-term vasorelaxation, counterbalancing the hypertensive and vasoconstrictive effect of atherosclerosis. Elastin peptides, circulating degradation products of extracellular matrix, could play a role in altering gene expression or influencing cell motility and differentiation (50).…”
Section: Physiological Function (Vasodilatation) Of Elastinmentioning
confidence: 99%